(untitled) (Revista de História Regional, 2020)
The physician Heráclides César de Souza-Araújo, from the southern Brazilian state of Paraná, was a prominent figure in the fight against leprosy in the country, beginning in 1916, a year after graduating from the Rio de Janeiro Faculty of Medicine. Souza-Araújo defended a prophylactic model based on the compulsory isolation of lepers, which was proposed and supported by a number of renowned scientists, such as Oswaldo Cruz. Although he originally intended to establish his program to combat leprosy in the state of Paraná, his plans were eventually implemented in the northern Brazilian state of Pará, where he helped to found the country’s first agricultural colony for lepers, in 1924. The present study explores the configuration of Souza-Araújo’s prophylactic model and his quest for social legitimization, following his trajectory through the analysis of texts published in the “A República” newspaper in Curitiba – Paraná, official documents and the book “Lazarópolis do Prata: the first agricultural leper colony founded in Brazil”, published in 1924, in which the author describes the implementation of his prophylactic program in the state of Pará.